(untitled) (New York, 2003)
Europe is waking up to the challenge of technology and innovation. We see EU commitment to spend 3% of GDP on Ramp;D, but who is thinking about how to spend? Who is thinking about technology management? Does the corporate Board have the means to manage this spending? Should some percentage of the Ramp;D be spent on improving technology and innovation management? This is where this book makes a contribution. It brings together the latest practice, research findings and thinking, presented in a way that addresses top management requirements. The goal is to secure the economic future of the firm, in the context of a sustainable industry and society. Using the ideas and methods in this book, the Board can assess and improve its own ability to deal with the challenge of technology and innovation.
Keywords: Technological innovations,Strategic planning,Industrial management,Organizational effectiveness; Management; European Union countries,European Union countries,European Union countries